Half and full sodium-ion batteries based on maize with high-loading density and long-cycle life. Issue 34 (15th August 2016) - Yang, Tingzhou; Niu, Xiaoying; Qian, Tao; Shen, Xiaowei; Zhou, Jingqiu; Xu, Na; Yan, Chenglin
Abstract : Sodium-ion batteries with an ultra-long cycling performance of ∼5000 cycles and a high mass loading density of 8.31 mg cm −2 were demonstrated. Abstract : Sodium-ion batteries are especially attractive in the field of sustainable and cost-effective energy storage devices as promising alternatives to lithium-ion batteries. In this work, a lamellar carbon anode derived from biomass byproduct maize husks (LCMH) and a suitable NASICON structured Na3 V2 (PO4 )3 cathode are utilized to assemble a full sodium-ion battery, which exhibits an extremely long cycle life of ∼1000 cycles and a high voltage of 4.1 V. More importantly, a stable reversible capacity of 239.6 mA h g −1 for the LCMH anode is obtained, along with an ultra-long cycling performance of ∼5000 cycles and a high mass loading density of 8.31 mg cm −2 . Significantly, in-situ X-ray diffraction measurements are introduced to reveal the Na-storage mechanism and structure evolution upon battery cycling. This strategy provides a brand-new direction for building advanced electrode materials for full sodium-ion batteries.